Azerbaijan’s family values and protecting them for the future generations - Ilahe Hajiyeva Dilkhosh (Scientific Research and Experimental Development, 2026)
Regardless of historical development, the institution of the family remains of primary importance to society and the state, serving as the foundation for the development and functioning of society. Currently, the understanding of family and family values ​​is undergoing a transformation. In some modern countries, the image of these institutions is changing, which is influencing the development and worldview of future generations. In particular, the most significant transformations have occurred in European countries and the United States, which have extended their influence to other Eastern countries, radically altering notions of family and attempting to impose their positions and views on our country. However, despite the proclamation of protection for the family and family values ​​in the aforementioned documents, legislation still lacks a clear definition of "family." The term is rather vague, and the concept of "family values" is not defined, leading to various debates. Analyzing family legislation, it can be noted that this term is quite common, but to date, it has only been present in legal doctrine. Consequently, the essence of "family" and "family values" and what specifically needs to be protected remain unclear.